1986
DOI: 10.3109/00365528609015162
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related Septicaemia in Patients Receiving Home Parenteral Nutrition

Abstract: Forty-three patients received home parenteral nutrition (HPN) for 4 to 13 months (median, 30 months) with a total treatment period of 153 patient-years. All patients had central venous catheters; 71 PVC subclavian catheters, 138 Broviac catheters, and 16 other catheters were used. Broviac catheters were introduced into the central veins via a tunnel on the chest (94 catheters) or on the thigh (44 catheters). Eighty-two episodes of catheter septicaemia occurred in 28 (65%) of the patients, corresponding to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 13 publications
2
25
0
4
Order By: Relevance
“…The body of experience gained so far and the resulting current recommendations confirm the justifiability of antibiotic lock therapy for the treatment of catheter-related infections without the need to remove the catheter in patients requiring longterm venous access [5,13,14]. Rannem et al successfully managed some of the infections solely with antibiotics administered through the catheter and Buchman et al, in patients treated between 1986 and 1989, managed to preserve 87% catheters using this method [15,16]. More recent studies, however, showed a greater efficacy of antibiotic lock therapy compared to antibiotic infusion through the catheter [17,18] and a longer survival of the dialysis catheter after lock therapy versus catheter replacement (154 and 71 days, respectively) [19].…”
Section: Discussionmentioning
confidence: 73%
“…The body of experience gained so far and the resulting current recommendations confirm the justifiability of antibiotic lock therapy for the treatment of catheter-related infections without the need to remove the catheter in patients requiring longterm venous access [5,13,14]. Rannem et al successfully managed some of the infections solely with antibiotics administered through the catheter and Buchman et al, in patients treated between 1986 and 1989, managed to preserve 87% catheters using this method [15,16]. More recent studies, however, showed a greater efficacy of antibiotic lock therapy compared to antibiotic infusion through the catheter [17,18] and a longer survival of the dialysis catheter after lock therapy versus catheter replacement (154 and 71 days, respectively) [19].…”
Section: Discussionmentioning
confidence: 73%
“…Most investigators accept a single positive blood culture from either a central or a peripheral sampliag site as evidence of catheter sepsis in a patient with symptoms of infection and no other apparent focus. Using that definition Danish studies have shown an incidence of catheter sepsis of 0.3-0.5 per catheter year with the Broviac catheter (62,63) comparable with the incidence of 0.55 per catheter year found in a large review of 2262 Broviac-Hickman catheters (64). Catheter sepsis seems more frequent in short-bowel patients than in non-short-bowel patients on parenteral nutrition (65), and in these patients it is more frequently caused by Gram-negative rods, whereas Staphylococci are the most commonly grown microorganisms in non-short-bowel patients (6.5).…”
Section: Complicationsmentioning
confidence: 64%
“…Catheter sepsis seems more frequent in short-bowel patients than in non-short-bowel patients on parenteral nutrition (65), and in these patients it is more frequently caused by Gram-negative rods, whereas Staphylococci are the most commonly grown microorganisms in non-short-bowel patients (6.5). Catheter sepsis is also more common when the line is inserted via the lower than via the upper extremity (63).…”
Section: Complicationsmentioning
confidence: 99%
“…Some authors have defined intravenous catheter-related septicaemia as the finding of a positive blood culture in the absence of a focus of infection other than the catheter itself [14,25]. Others point out that catheter-related septicaemia can only be determined by the identification of an identical organism in a culture of the catheter segment and in a peripheral blood culture [7,18,19].…”
Section: Discussionmentioning
confidence: 97%
“…Septicaemia resulting from an intravenous catheterization runs a mild course and the incidence is presumed to be less than 1% even in high-risk patient populations [3,15,25]. Staphylococcus aureus septicaemia as a sequel to injections is predominantly a 306 M. Tsokos, K. Püschel: Staphylococcus aureus-induced septicaemia complication found in intravenous drug abusers [4,12,28], in patients with progressive and disseminated malignancy [5] or in patients requiring long-term intravascular access [20,25]. The immunocompromisation brought about by the severity of the underlying illness is presumed to be a major determinant of mortality [5,30].…”
Section: Discussionmentioning
confidence: 99%